Influence of mother's oral health care knowledge on oral health status of their preschool child - Raghavendra M Shetty; Anushka Deoghare; Sujata Rath; Rasna Sarda; Abhishek Tamrakar (Wolters Kluwer Medknow Publications, 2016)
Aim: Children under 5 years of age generally spend most of their time with parents or guardians, especially mothers. Parents play a central role in giving children the information and encouragement needed for healthy lives. Parental oral health knowledge, belief and attitudes influence the oral health maintenance, dietary habits and healthy behavior of their children. The aim of this study was to assess the mothers oral health care knowledge and to assess the oral health status of their child. Materials and Methods: A total of 386 mothers along with their child of 1-6 years were randomly selected for the study. A 22-point questionnaire including parent's literacy levels, socioeconomic status, dietary practices and oral hygiene practices, was designed to assess the knowledge of the mothers regarding oral health of their child. Oral examination of the children was done by World Health Organization criteria for recording children's oral health status. Results: About 87% of the mothers agreed that intake of food with excessive sugars can cause cavities, and 95.8% admitted that chocolates cause the most decay. 80.5% agreed to the fact that leaving a milk bottle all night increases the risk for tooth decay, however, 59.3% mothers were of the opinion that dental visit is must only in the presence of decay. 59.3% mothers were unaware about the optimal fluoride content. 71.7% mothers agreed that caries in deciduous teeth are a matter of concern. The average decayed score of the children was 2.9 and 77.9% of the children had a fair to good oral hygiene status. Conclusion: Instead of the fact that most of the health care knowledge that the mothers had was primarily from the family elders, they were aware of caries risk factors, tooth brushes and amount of toothpaste and bacteria from mother's cavities can infect child. This could be observed by less number of decayed teeth and good oral hygiene status of the children. However, parents knowledge, attitudes and few beliefs regarding dental care need to be improved.